2020
DOI: 10.1186/s12903-020-1012-1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental implantoplasty outcomes correlate with fibroblast growth in vitro

Abstract: Background: Implantoplasty is an option in peri-implantitis treatment, but little is known about the effect on the soft tissue. The aim of the study was to characterize surface roughness following experimental implantoplasty and to examine its effect on human fibroblast growth and secretion of selected proteins.Methods: Titanium grade IV coins were mechanically treated with six different rotating bur sequences; diamond burs or carbide burs alone, or followed by either Arkansas stone bur or silicone burs. Machi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…In the present study, surface roughness values after all IP procedures were higher than those of machined surface and, with the exception of SONIC, lower as compared to Osseotite ® . In agreement with other studies (Beheshti Maal et al., 2020; Ramel et al., 2016; Sahrmann et al., 2019), Arkansas finishing smoothed the surface leading to similar roughness between SONIC + A and BUR + A. Raoofi et al, examined the surface roughness obtained by using a sequence of two diamond inserts mounted on a piezosurgery device, obtaining greater values of Ra (1.21 µm, SD 0.26) and Rz (3.94 µm, SD 1.16) (Raoofi et al., 2013). Ra values measured in SONIC + A were similar to those obtained in another study using a sequence of diamond burs followed by a Greenie silicone polisher (Ra 0.59 µm, SD 0.19; Rz 4.35 µm, SD 1.37) (Ramel et al., 2016).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In the present study, surface roughness values after all IP procedures were higher than those of machined surface and, with the exception of SONIC, lower as compared to Osseotite ® . In agreement with other studies (Beheshti Maal et al., 2020; Ramel et al., 2016; Sahrmann et al., 2019), Arkansas finishing smoothed the surface leading to similar roughness between SONIC + A and BUR + A. Raoofi et al, examined the surface roughness obtained by using a sequence of two diamond inserts mounted on a piezosurgery device, obtaining greater values of Ra (1.21 µm, SD 0.26) and Rz (3.94 µm, SD 1.16) (Raoofi et al., 2013). Ra values measured in SONIC + A were similar to those obtained in another study using a sequence of diamond burs followed by a Greenie silicone polisher (Ra 0.59 µm, SD 0.19; Rz 4.35 µm, SD 1.37) (Ramel et al., 2016).…”
Section: Discussionsupporting
confidence: 94%
“…The combination of diamond burs and Arkansas stones for IP resulted in a smooth implant surface allowing the adhesion of subepithelial connective tissue in vivo (Schwarz et al., 2011). The use of Arkansas as a polishing procedure is preferable than silicone polishers as it does not cause silicone debris contamination of both implant surface and peri‐implant tissues (Beheshti Maal et al., 2020; Costa‐Berenguer et al., 2018; Ramel et al., 2016; Tawse‐Smith et al., 2016). It has been suggested that the release of Ti micro‐ and nano‐particles from dental implants, such as following IP, can stimulate a number of cytokines, which, in turn, sustain a local inflammatory response (Kumazawa et al., 2002; Noronha Oliveira et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to 15 years ago, only 1 case report was published advocating "implantoplasty" as surface detoxification method. 28 In December 2020, 14 articles were published, [29][30][31][32][33][34][35][36][37][38][39][40][41][42] where in-vitro studies are dominant. Therefore, it seems that there is a growing interest in this approach as adjunctive therapy to peri-implantitis; nonetheless, evidence is sparse.…”
Section: Agreements and Disagreements With Previous Studiesmentioning
confidence: 99%
“…Ideally, this adjunctive treatment may result in an implant surface which impedes bacterial colonisation and facilitates soft tissue adaption. Several in vitro studies have demonstrated that smooth implant surfaces may enhance fibroblast growth compared to rough surfaces [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%